UPON THE BORDERS OF MACEDONIA SECUNDA – FACTS, ASSUMPTIONS, CONSIDERATIONS (Annual of the Faculty of Philosophy in Skopje, 2019)
The borders of the Roman Empire, which fluctuated throughout the empire'shistory, were a combination of natural frontiers and man-made fortifications whichseparated the lands of the empire from the ”barbarian” lands beyond. In assessingthe territory of the Roman Empire, we can observe different geographical and artificialadministrative demarcations. At the outskirts we have the frontiers that determinedthe physical edges of the empire, which established not only the Empire’s sizegeographically, but also designated the limits of the territory that was to be ruled bythe Empire’s administration. The expansion of the empire in the Late Republic and(early) Empire led to an increase of provincial territories and thus of provincial boundariesor borders, separating the different provincial territories from each other.The sources of the topography of Macedonia in the Roman period are verypoor despite the many geographical and historical works that treat its territory. Forthe gradual alteration and redefinition of administrative boundaries, the creation ofnew and the abolition of the old provinces, the sources offer a fragmented picture,while offering only partial details on the definition of the boundaries. In this regard,the attempt to define the exact boundaries between the late antique provinces is basedon several reliable facts and many assumptions.
Keywords: LATE ANTIQUE; ROMAN PROVINCES; ADMINISTRATION; MACEDONIA; BORDERS